Bachelor of Nursing students' HIV and AIDS knowledge in KwaZulu-Natal province: An evaluation study - Silingene J. Ngcobo; Gugu G. Mchunu (AOSIS, 2019)
Background: Currently, human immunodeficiency virus and acquired immunodeficiency syndrome (HIV and AIDS) education and training in nursing suffer from various inadequacies and lack any real formalisation in their governance. As a result, Bachelor of Nursing students find themselves challenged in providing effective HIV and AIDS healthcare management, largely because of the deficit in training identified. An HIV and AIDS education intervention programme was introduced at a selected KwaZulu-Natal university to assist in bridging the perceived knowledge gap. This article communicates programme evaluation findings. Objectives: The aim of this article was to determine levels of HIV knowledge achieved following an HIV education intervention programme. Methods: A pure, descriptive quantitative research design was employed, using total population sampling (N = 133). A modified G3658-11 Collecting Evaluation Data: End-of-Session Questionnaire, developed by the University of Wisconsin-Extension, was administered for data collection. Results: Females predominated in the study, and most participants were African with 1 to 3 years of education programme exposure. Perceived HIV knowledge increase was evident: pathophysiology (n = 93, 70.2%); immunology (n = 97, 72.9%); transmission (n = 116, 87.5%); diagnosis (n = 109, 81.8%); prevention strategies (n = 118, 88.4%); staging and monitoring (n = 106, 80%); pre- and post-test counselling (n = 104, 78%). Conclusion: Pre- and ongoing in-service HIV and AIDS training can improve perceived HIV knowledge levels for both nursing students and professionals. Mandatory HIV and AIDS healthcare management training is therefore recommended in planning for its effective impartation by nursing educators.